Immunohistochemical expression of P16 and HER2/neu in normal oral mucosa, oral epithelial dysplasia, and oral squamous cell carcinoma - Suha A Ahmed; Ahlam H Majeed (College of Dentistry/ University of Baghdad, 2014)
Background: Oncogenesis in the oral cavity is widely believed to result from cumulative genetic alterations that cause a transformation of the mucosa from normal to dysplastic to invasive carcinoma. The p16 gene produces p16 protein, which in turn inhibits phosphorylation of retinoblastoma (Rb), p16 play a significant role in early carcinogenesis. A number of epidermal growth factor receptor (EGFR) family, HER2/neu, has received much attention because of its therapeutic implications. The aims of the study were to evaluate and compare the immunohistochemical expression of the cell cycle protein P16 INK4a and c-erbB2 (HER2/neu) in NOM, OED, and OSCC. Correlate both marker expression with each other as well as with various clinicopathological findings. Materials and methods: Sixty two formalin-fixed, paraffin embedded tissue blocks (20 cases of normal oral mucosa, 17 cases of oral epithelial dysplasia, and 25 cases of oral squamous cell carcinoma) were included in this study, an immunohistochemical staining was performed using anti p16 monoclonal antibody, and anti HER2/neu polyclonal antibody. Results: Positive IHC expression of p16 was found in 18 cases (90%) of NOM, 16 cases (94.1%) of OED and in 20 cases (80%) of OSCC. Positive IHC expression of HER2/neu was almost undetectable in NOM, while it was found in 9 cases (52.9%) of OED, and in 15 cases (60%) of OSCC.The correlation between the expression of both markers were statistically highly significant in NOM, significant in OED, and non significant in OSCC. Conclusions: This study signify the important role of p16 and HER2/neu in oral carcinogenesis and in the evolution of the mucosa from normal to dysplastic to invasive carcinoma